STATE'S LEGAL PRIORITY AS A CREDITOR IN ENVIRONMENTAL BANKRUPTCY PROCEEDINGS - Kadir, Nadiah Khaeriah; Dahlan, Muhammad Fitratallah; Mathen, Yoyada Palinggi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Cases of corporations unable to pay fines for environmental damage continue to increase, with bankruptcy often chosen as a means to resolve such liabilities. This study aims to analyze the legal protection of the state as a preferred creditor in cases of corporate bankruptcy caused by environmental harm, with a case study of PT Ricky Kurniawan Kertapersada. The research employs a qualitative method using legislative, case, and comparative approaches to examine Indonesia’s bankruptcy law. The novelty of this research lies in the idea of recognizing environmental debts as “ecological preferred claims” and the urgency of progressive legal mechanisms to safeguard the state’s right to environmental recovery even when companies go bankrupt. The findings show that Indonesia’s bankruptcy regulation remains privatistic and fails to accommodate ecological justice, often neglecting state claims. Therefore, this study recommends amending Law No. 37 of 2024 on Bankruptcy and PKPU.